AB1107 Assessment of agreement between self-report inflammatory arthritis symptoms and corresponding gp diagnosis in patients with pmr. (15th June 2017) - Hider, SL; Blagojevic-Bucknall, M; Muller, S; Clarkson, K; Mallen, C
Abstract : Background: Polymyalgia rheumatica (PMR) is the commonest inflammatory condition among those aged 50 years and over, with a lifetime risk of 2.4% in females and 1.7% in males. Seronegative rheumatoid arthritis is an important differential diagnosis. It is thought a proportion of PMR patients develop an inflammatory arthritis, although prevalence estimates vary. Objectives: To determine the proportion of PMR patients (1) reporting symptoms of possible inflammatory arthritis using a validated self-report inflammatory arthritis algorithm; and (2) who subsequently receive a diagnosis of inflammatory arthritis in their primary care medical records. Methods: A cross-sectional questionnaire study was developed to investigate impact of PMR in primary care patients. All eligible adults aged ≥50 years, registered with one of 150 participating practices with a first ever Read coded diagnosis of PMR in the last 3 years were mailed a questionnaire including items about socio-demographics, PMR characteristics, joint problems and comorbid conditions. Self-reported inflammatory arthritis (IA) was defined using a validated scoring algorithm (1) with positive responses coded as 1 and negative responses as -1; a score >0 is regarded as predictive of IA. IA score was calculated for those patients that had complete data on all required variables. A list of Read Codes relating to inflammatory arthritis, compiled by a rheumatologist and a GP, were searched for in primary care medical records of consenting respondents. Period of interest was from date of first ever PMR diagnosis in the medical records until survey mail-out. Results: 704 eligible patients were identified and sent a questionnaire, with 550 (78%) responding. Responders and non-responders did not differ significantly by age or gender. Medical records could be obtained for 385 patients, of whom 310 completed the questionnaire fully and were included in the analysis. IA score ranged from -8.4 to 2.5, with 21 (7%) patients being classed as having a positive IA score. 8 out of 310 patients had at least one inflammatory arthritis Read code recorded from date of first diagnosis of PMR in their medical record, although only 2 of these also fulfilled the self-report IA criteria. Conclusions: In this PMR cohort the proportion subsequently diagnosed with an inflammatory arthritis was low (2.5%) although more patients reported inflammatory symptoms. The agreement between self-reported inflammatory symptoms and Read Code diagnosed inflammatory arthritis was low. References: Tavares R, Wells GA, Bykerk VP et al. A a parallel group cohort to determine the measurement properties of an early inflammatory arthritis detection tool. Rheumatology 2013;52:2077–2085. Acknowledgements: This study represents independent research funded by the National Institute for Health Research (NIHR). CDM is funded by the National Institute for Health Research (NIHR) Collaborations for Leadership in Applied Health Research and Care West Midlands, the NIHR School for Primary Care Research and a NIHR Research Professorship in General Practice (NIHR-RP-2014–04–026). The views expressed are those of the authors and not necessarily those of the NHS, NIHR or the Department of Health. Disclosure of Interest: None declared